Root-zone hypoxia reduces growth of the tropical forage grass Urochloa humidicola in high-nutrient but not low-nutrient conditions - Jiménez Serna, Juan de la Cruz; Kotula, Lukasz; Veneklaas, Erik Jan; Colmer, Timothy D. (Oxford University Press, 2019)
Abstract Background and Aims The perennial C4 grass Urochloa humidicola is widely planted on infertile acidic and waterlogging-prone soils of tropical America. Waterlogging results in soil anoxia, and O2 deficiency can reduce nutrient uptake by roots. Interestingly, both nutrient deficiencies and soil waterlogging can enhance root cortical cell senescence, and the increased gas-filled porosity facilitates internal aeration of roots. We tested the influence of nutrient supply and root-zone O2 on root traits, leaf nutrient concentrations and growth of U. humidicola.